Philosophy and Arts in the Islamic World - Vermeulen, Urbain 1940-2016; De Smet, D. (Leuven Peeters, 1998)
The volume contains 26 contributions to literature, philosophy, linguistics and epigraphy in Islamic culture, ranging from pre-Islamic poetry to contemporary prose, from the Ihwan as-Safa to the theology of Mawdudi, from lexicography to epigraphy. These papers were read at the Eighteenth International Congress of the Union Europeenne des Arabisants et Islamisants, organized by the Catholic University of Leuven (KUL) from 3 to 10 September 1996. A second volume of proceedings, that appears along with this one (OLA 86), is more concerned with questions of actuality and political organisation, including Christian minorities in the Arab world, in their relation to the Muslim environment. As such the two volumes put together, will provide to the world of learning, we may say, an overall picture of the current scientific investigations about Islamic culture and society. Series: Orientalia Lovaniensia Analecta, 87Summary:The volume contains 26 contributions to literature, philosophy, linguistics and epigraphy in Islamic culture, ranging from pre-Islamic poetry to contemporary prose, from the Ihwan as-Safa to the theology of Mawdudi, from lexicography to epigraphy. These papers were read at the Eighteenth International Congress of the Union Européenne des Arabisants et Islamisants, organized by the Catholic University of Leuven (KUL) from 3 to 10 September 1996. A second volume of proceedings, that appears along with this one (OLA 86), is more concerned with questions of actuality and political organisation, including Christian minorities in the Arab world, in their relation to the Muslim environment. As such the two volumes put together, will provide to the world of learning, we may say, an overall picture of the current scientific investigations about Islamic culture and society.
Proceedings of the 18th Congress of the Union européenne des arabisants et islamisants held at the Katholieke Universiteit Leuven
Keywords: Philosophy; Fine art; Islam; Arabia